Involvement of Year‐to‐Year Variation in Thermal Time, Solar Radiation and Soil Available Moisture in Genotype‐by‐Environment Effects in Maize. Issue 5 (1st September 2016) - Lee, E.A.; Deen, W.; Hooyer, M.E.; Chambers, A.; Parkin, G.; Gordon, R.; Singh, A.K.
Abstract : Year‐to‐year variability in temperature, precipitation, and solar radiation is increasing due to global climate change. This enhanced variation will likely lead to more frequent and larger genotype‐by‐environment interaction (G × E) effects impacting genetic gains from selection. In this study G × E effects are examined in the absence of genetic variation for thermal time requirements (i.e., phenology), with an understanding of which physiological mechanisms are responsible for genotypic differences in grain yield, using a series of developmental windows, and in the context of fully characterized environments. Using a set of hybrid RILs of the classic Iodent × Stiff Stalk heterotic pattern, we demonstrate that the hybrid RILs are phenologically uniform and that grain yield differences are due primarily to genetic variation in dry matter accumulation during the grain filling period. We demonstrate that annual fluctuations in thermal time and solar radiation during key windows of development are causing G × E effects, and that variation in soil available water is not a major contributor to the G × E effects. Finally, we present evidence to support the concept that G × E effects resulting in crossover interactions occur due to how the genotypes respond to environmental factors that impact development, while G × E effects resulting in changes in magnitude arise due to variation in how genotypes respond to growth‐related environmental parameters.